#146 Development and characterization of geniste in nano structured lipid carriers loaded topical nanogel to target melanoma cells - Lakshmi; Singh, Sanjay; Soni, Surabhi (Journal of Pharmaceutical Chemistry, 2022)
The aim of the present study was to develop topical nanogel utilizing genistein loaded nanostructured lipid carriers (GEN-NLCs) in order to provide a controlled release and targeting skin epidermis. The different batches of GEN-NLCs were prepared by solvent diffusion method using orthogonal Taguchi optimization design. Then, GEN-NLCs were evaluated for various physicochemical parameters like particle size, zeta potential, entrapment efficiency, and in-vitro drug release studies. Morphological studies were performed using scanning electron microscopy and atomic force microscopy. Moreover, in-vitro anticancer studies and cellular uptake studies by fluorescence microscopic studies were performed on A-375 melanoma cell lines. GEN-NLCs loaded gels were prepared utilizing methocel and characterized for particle size and texture profile analysis (TPA). Further, the optimized gel was evaluated for in-vitro and ex-vivo occlusion test, in-vitro release study, ex-vivo human skin permeation & retention study. GEN-NLCs were found to be in the nanometric range with 89.50% entrapment efficiency and -14.98 mV zeta potential. Release studies confirmed the controlled release nature of the NLCs. In-vitro anticancer activity by MTT assay revealed that the nanoparticles were found to be 15.37 times more effective against melanoma as compared to the drug, whereas fluorescence studies confirmed enhanced cellular uptake with time. The results of the evaluation of gel indicated that there is no significant change in the texture profile of hydrogel after incorporating GEN-NLCs having 3% of methocel gel. GEN-NLCs loaded gels showed an occlusion factor almost 3.45 times higher than control gel at the end of 24 h resulting in a significant increase in the occlusivity of the hydrogel. In-vitro release kinetic data of Genistein exhibited the sustained release of drug which follows Higuchi release kinetics ex-vivo studies further confirmed a decrease in flux across the skin, i.e., controlled release pattern of GEN from hydrogel and increased hydration and retention in the epidermis. Topical delivery of GEN-NLCs loaded gel showed a potential delivery system to target skin epidermis for melanoma cancer.